(untitled) (Zoo Botanica, 2025)
The traditional methods of sowing sugarcane crop have serious gaps that result in low crop yield and high cost of production. These gaps are high seed rate, high cost of seed material, low plant population and poor seed quality at farmer field level. The adoption of bud chip technology offers a sustainable and efficient path for sugarcane production to remove the mentioned gaps in traditional methods. However, its full benefits can only be achieved by optimizing cultivation techniques. Plant spacing is particularly a critical factor that needs to be investigated. To address this, a field experiment was conducted in spring 2021 at the Sugarcane Research Institute, AARI, Faisalabad. The crop was sown on 15 February 2021 and harvested on 25 December 2021. Randomized complete block design under Split Plot arrangements was used to lay out experiment, with three replications. The treatments included three plant spacing viz. 30 cm, 60 cm, 90 cm and three sugarcane genotypes viz. CPF-251, CPF-253, CP00-1101. The results depict that the 60 cm plant spacing consistently resulted in the highest cane yield (67.31 t/ha), sugar yield (7.84 t/ha), and sugar recovery (11.61%) for CPF-251. For the CPF-253 and CP00-1101 clones, the 30 cm plant spacing was more effective. This spacing created the highest values for cane yield (110.91 t/ha), sugar yield (13.12 t/ha) and sugar recovery (11.86%). It was concluded that the ideal plant spacing is variety-specific, and 60 cm plant spacing is optimum in sugarcane cultivation using bud chip technique. This technique is a cost-effective alternative to conventional sett planting, reduces the quantity and cost of seed cane required with a seed saving of 73–77% over traditional sett planting.